Kant’s categories of freedom - Mumbrú Mora, Álex (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
Starting from an understanding of Kant’s trascendental method that does not limit its field of application to the theoretical domain, the main aim of this paper is to analyze the nature, function and systematic place of the categories of freedom as elementary practical concepts, considering both the external and internal use of freedom. For that purpose, we will bring out the strict parallelism that exists with the theoretical categories, as well as their mutual foundation in the trascendental apperception as last ground of both spheres of objectivity.